The Effect of Using Flipped Classroom Strategy on Application of Rules of Recitation and Memorization of Quranic Verses - Alayasrieh, Mohammed; Alshabibi, Thuraya (Dirasat: Educational Sciences, 2021)
The study aims to reveal the effect of using the flipped classroom strategy on applying the rules of recitation and memorizing Quranic verses in Islamic Esducation course. To achieve this, the researchers used a quasi-experimental approach. The sample of the study consisted of (137) female students, who were divided into two groups: an experimental group that included of (71) female students and a control group that included (66) female students. An oral test for the rules of recitation and written memorization tests for verses were prepared. The study materials (teacher’s guide, activity booklet, assignment file, and preparation log) were also prepared. The study concluded that there is a statistically significant difference between the mean scores of the experimental and control groups in the post application of the oral test of recitation rules and in the written memorization tests due to the teaching method in favor of the experimental group. In addition, there was a statistically significant difference in the application of the rules of recitation and in the written memorization tests among eighth grade students due to achievement in favor of the experimental group with high academic achievement.